Sustainable Policy Interventions for Coastal Erosion affecting Eco-Tourism and Development in Bali, Indonesia - Viswanath Ayyagari, Saurav; Komang Wulan Aprilia, Gusi; Mehmoud Fawaz, Nabil (Indonesian Association for Public Administration (IAPA), 2024)
Coastal erosion imposes an looming barrier to eco-tourism and sustainable development in Bali, Indonesia. As a premier international tourist destination, Bali's economy and cultural identity are inextricably correlated to its coastal beach environements. Though, climate change increasingly stresses this island's fiscal and environemental resources. Rising sea levels compounded with anthropogenic pressures accelerates coastal erosion and degradation. This multi-facted IAPA conference paper will investigate risk and crisis management with data-informed adaptive proposals to protect environmental values. The following sustainable policy intervention approaches coastal erosion with a focus on preserving eco-tourism assets and development opportunities in Bali. The research methodology synthesizes recent literature on coastal vulnerability, greeen erosion mitigation, spatiotemporal climate projections, and preventative adaptation strategies specific to Bali and similar coastal tourism destinations. This conference paper proposes that an integrated coastal zone management approach combining organic solutions, adaptive governance, and sustainable tourism practices offers the most promising framework to address coastal erosion while promoting Bali's eco-tourism sector. The central thesis argues that effective coastal erosion management in Bali requires coordinated policy interventions across multiple scales of governance, coupling robust scientific monitoring with flexible, context-specific adaptation measures and stakeholder engagement.